Innovation Smart Farm and Garden; Islamic Boarding School Islamic Studies Center Aswaja Lintang Songo, Bantul - Baidawi Alvaro; Hamdan Daulay (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2023)
The threat of a food crisis faced by a number of Islamic boarding schools today is clear. One of them is the Islamic Studies Center Aswaja Lintang Songo Islamic Boarding School, Bantul Regency. Therefore, this pesantren has a smart farm and garden innovation to supply food needs and boost the pesantren's economic sector. The idea was initiated by Kiai Heri Kuswanto as the caretaker of the Lintang Songo Islamic Boarding School who was assisted by all his students in their activities, especially on agricultural land and plantations. Smart Farm and Garden is an integrated management of the agricultural and plantation sectors using modern technology. This study aims to find out how the smart farm and garden innovation process is practiced in the field. The research method used is descriptive qualitative with the type of research field research (field research). Data collection techniques include observational studies, interviews and documentation. The results of this study are smart farm and garden innovations to grow a new economy based on the entrepreneurial sector. This idea also has a positive impact on the birth of santri independence in managing agriculture and plantations. The harvest will be exported to several areas in the Special Region of Yogyakarta DIY for the income of Islamic boarding schools, so that the financial budget is well fulfilled.